2017
DOI: 10.1155/2017/8769402
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain in Children: A Look at the Referral Process to a Pediatric Pain Clinic

Abstract: We reviewed the referral pattern of children with chronic pain to a specialized pediatric pain clinic. Data were obtained from referring physicians and medical records and during an interview with patients and their parents by physicians and a psychologist. We analyzed the following: referral diagnosis, demographics, duration of symptoms, number of physicians previously consulted, school attendance, sports activities, presence of psychological disorders, final team diagnosis, and outcomes. Children had been ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 34 publications
(34 reference statements)
1
42
0
2
Order By: Relevance
“…There are two important aspects of chronic pain in children and adolescents: the delay in referring these patients to a pediatric pain specialist, and the failure to recognize psychological disorders as an important comorbid condition in chronic pain [51]. Often, lack of an identifiable etiology along with the complex biopsychosocial nature of this condition leads to a lengthy diagnostic odyssey and delayed treatment that exacerbates the existing problem [52].…”
Section: Discussionmentioning
confidence: 99%
“…There are two important aspects of chronic pain in children and adolescents: the delay in referring these patients to a pediatric pain specialist, and the failure to recognize psychological disorders as an important comorbid condition in chronic pain [51]. Often, lack of an identifiable etiology along with the complex biopsychosocial nature of this condition leads to a lengthy diagnostic odyssey and delayed treatment that exacerbates the existing problem [52].…”
Section: Discussionmentioning
confidence: 99%
“…Cucchiaro et al assessed the time length of the referral processes to a specialized pediatric pain clinic; and found that children on their series experienced pain for 34 ± 55 months. In pediatric chronic pain programs, interventional procedures are usually introduced when other conservative treatment modalities have failed .…”
Section: Discussionmentioning
confidence: 99%
“…CPPs had higher scores in the items anxiety/depression of CBCL and anxiety/shyness of CPRS scales with respect to CGPs, with a statistically significant difference. Several previous studies showed that comorbid depression and anxiety were common in chronic pain patients (Cooper et al, 2017; Cucchiaro et al, 2017; Cunningham et al, 2016; Gureje, 2007; Khan et al, 2015; Martínez, Gómez-Restrepo, Ramírez, & Rodríguez, 2016; Simons, Sieberg, & Claar, 2012; Vinall, Pavlova, Asmundson, Rasic, & Noel, 2016; Zis et al, 2017). Neurobiological factors (genes, hormones, and neural networks) shared between chronic pain and symptoms of psychological distress such as anxiety and depression may partly explain their co-occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in adults, previous studies have found that chronic pain is associated with increased suicide ideation independent of depression (Margari et al, 2013; Miller, Hopkins, & Whorwell, 2004). Anxiety and depression symptoms in turn (Cucchiaro et al, 2017; Cunningham et al, 2016; Khan et al, 2015; Martínez et al, 2016; Simons et al, 2017; Vinall et al, 2016), may play a key role in the maintenance of disability, driving them to avoidant behaviors and perpetuating a vicious cycle, which may further decrease youth quality of life (Cunningham et al, 2016; Simons et al, 2012; Tarantino et al, 2013; Vinall et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation